2020
DOI: 10.13005/ojc/360424
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Bioactive Components of Sweet Basil (Ocimum basilicum Linn.), Luyang dilaw (Curcuma longa Linn.) and Lagundi (Vitex negundo) as Inhibitor against Human Immunodeficiency Virus (Hiv-1)

Abstract: Human Immunodeficiency Virus (HIV-1) has glycoproteins gp41 and gp120 use to attached to the host cell. Development of antiviral drug use in silico drug design to select potent lead molecule from medicinal plants. Bioactive components of Sweet basil (Ocimum basilicum Linn.), Luyang dilaw (Curcuma longa Linn.), Lagundi (Vitex negundo) were used as ligands to inhibit HIV-1 gp120 and gp41 using ArgusLab Software. Inhibition of gp120, results showed that the α-Guaiene from Sweet basil has the lowest binding affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The binding affinity (or free energy of binding) is the sum of the final intermolecular energy and torsion-free energy. The negative value of binding affinity depicts that the reaction between bioactive components bonded to the active site occurs spontaneously due to this change in total intermolecular and torsional energies [28]. Therefore, a better inhibitor of the Tat C protein among the selected ligands is the phenolic compound(s) with a high negative value of binding affinity as this corresponds to better bonding of phytochemical components with the receptor; better inhibition of the viral transcription, which then a better inhibition of the virus.…”
Section: Interactions and Mechanisms Of The Ligand-protein Complexes ...mentioning
confidence: 99%
“…The binding affinity (or free energy of binding) is the sum of the final intermolecular energy and torsion-free energy. The negative value of binding affinity depicts that the reaction between bioactive components bonded to the active site occurs spontaneously due to this change in total intermolecular and torsional energies [28]. Therefore, a better inhibitor of the Tat C protein among the selected ligands is the phenolic compound(s) with a high negative value of binding affinity as this corresponds to better bonding of phytochemical components with the receptor; better inhibition of the viral transcription, which then a better inhibition of the virus.…”
Section: Interactions and Mechanisms Of The Ligand-protein Complexes ...mentioning
confidence: 99%
“…A computational study demonstrated that this plant has the potential for antiviral drug development through its mechanism of inhibiting the active site of human immunodeficiency virus (HIV) gp120 and gp41. α-guaiene is the compound with the highest negative value for binding affinity, which was −9.62 Kcal/mol at the active site gp120, and sitosterol displayed a binding affinity for −10.99 Kcal/mol at the active site gp41 [ 79 ]. Furthermore, an in vitro study of the crude ethanolic extract of O. basilicum L. leaves demonstrated antiviral activity against Zika virus (ZIKV) with 97% virus infectivity at the highest concentration (1:16 dilution) [ 80 ].…”
Section: Antimicrobial Activities and Biomedical Usesmentioning
confidence: 99%